Association between gene polymorphisms of IL‐12, IL‐12 receptor and IL‐27 and organ involvement in Iranian endometriosis patients. (3rd November 2022) - Zare, Maryam; Hesampour, Fatemeh; Poordast, Tahereh; Valibeigi, Maryam; Enayatmehri, Maliheh; Ahmadi, Sahar; Nasri, Fatemeh; Gharesi‐Fard, Behrouz
Abstract: Endometriosis is an inflammatory disease characterized by the presence of ectopic endometrial tissue, immune cell dysfunction and abnormal cytokine secretion. In addition to immunological factors, genetic variations that influence endometriosis severity and cytokine expression levels play important roles in the pathogenesis of this disease. Interleukin‐12 (IL‐12), specifically its p40 subunit encoded by IL‐12B gene and the interleukin‐12 receptor β1 (IL‐12Rβ2) chain of its receptor, as well as interleukin‐27 (IL‐27) are important in the establishment of endometriosis. So, in this study, we measured IL‐12 and IL‐27 serum levels and investigated the possible links between IL‐12B rs3212227, IL‐12Rβ2 rs3790565 and IL‐27 rs153109 polymorphisms and the risk of developing endometriosis in a group of Iranian women. In this case‐control study, 162 endometriosis patients and 151 healthy women were included and tested for the aforementioned polymorphisms using the polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) technique. The enzyme‐linked immunosorbent assay (ELISA) method was also used to measure IL‐12 and IL‐27 serum levels. Although there was no statistically significant association between the genotypes and alleles of the studied polymorphisms and the development of endometriosis in general, the AA genotype of IL‐12B rs3212227 showed a significant association with uterine endometriosis when compared to AC+CC genotypes ( p = .04, CI = 0.270–0.988, OR = 0.517). Indeed, the AA genotype of the IL‐12B rs3212227 single nucleotide polymorphism (SNP) may be linked with a lower risk of developing uterine endometriosis. There was no significant difference in IL‐27 levels between the two studied groups ( p = .49), and IL‐12 levels were undetectable in both groups. In conclusion, the AA genotype of IL‐12B rs3212227 might be associated with a decreased risk of uterine involvement in endometriosis patients.